Clinical and epidemiological features of community-acquired sepsis Hospital Central Universitario Dr. Antonio María Pineda (Boletin Médico de Postgrado, 2022)
Community-acquired sepsis is a difficult syndrome to define, diagnose and treat. For this reason, a descriptive, cross-sectional study was carried out with the aim of describing the clinical and epidemiological features of patients with a diagnosis of community acquire sepsis admitted to the Internal Medicine Service of the Hospital Central Universitario Dr. Antonio Maria Pineda during the January-July 2019 period. 42 medical records were reviewed; the age group between the 46 and 75 years old represented 52% of the sample, 52% were male and 35% had several comorbidities. The main cause of sepsis was urinary tract infection (31%) followed by the mixed etiology in 28.6% individuals. Among paraclinical variables, 76.2% of the patients presented anemia and leukocytosis, 61.9% thrombocytopenia and 85.7% hyperazoemia. Regarding the hemodynamic variables, 66.7% showed tachycardia, 76.2%, tachypnea and arterial hypotension, 66.7% oxygen desaturation, 88% oliguria and 71.4% presented altered state of consciousness. Mixed organic dysfunction occurred in 83.3% of cases. 76.2% of patients died due to sepsis. Clinical and epidemiological data of community-acquired sepsis is a way to comprehend the behavior of this entity in order to carry out and adequate diagnosis and treatment and reduce the morbidity and mortality.
Keywords: sepsis; medical records; anemia; arterial hypotension; tachycardia